Peran Public Relation Tak Sekedar Fungsi Teknis - Masykuri, Nurul Candrasari (Humaniora, 2011)
Article explored many functions of Public Relations (PR). It is one department in an organization that is responsible for matters relating to community relations and has responsibility for the company image. PR is also responsible for inter-departmental relationships that exist within the organization. So, not only outward, but inward. PR bridges all the problems that occur between departments. In maintaining and improving the quality of image, PR will create a lot of programs to promote the company to the center of the community. The essence of PR must prepare and obtain more data concerning these trends through surveys, research, and observation in the intensive and continuous. The function of PR is essential in every point of planning and corporate development. PR should know the effects of packaging a product that will be offered to customers which will become regular customers of these products. In fact, a PR should be able to maintain such image what would happen if the packaging is yellow and what effect if replaced by a red color.